Pertanggungjawaban Pidana Penempatan Keterangan Palsu Pada Label Produk (Studi Kasus PT. Garam (Persero)). - Hendra Septyan Silitonga; T. Keizerina Devi Azwar; Abdul Aziz Alsa (Jurnal Hukum Lex Generalis, 2025)
The case of PT. Garam (Persero) decided through Supreme Court Decision Number 36 K/Pid.Sus/2019 has become an important spotlight in criminal law discourse regarding liability for placing false information on food product labels. This normative juridical research examines three main aspects: the form of false information placement, the mechanism for proving the element of intent, and considerations in determining the subject of criminal liability in the case. The analysis shows that there is proven placement of false information in the form of stating that salt was produced in Sampang from local raw materials when in fact it originated from Australian imports and was produced in Gresik, violating Permendag No. 125/M-DAG/PER/12/2015. The element of intent has been fulfilled through proof of awareness, consequences of the action, and consciousness in performing the action by Managing Director Dr. Ir. R. Achmad Budiono, M.M. who was designated as the subject of criminal liability based on his position as the highest leader with the application of identification theory. However, there are critical arguments regarding the weakness of evidence and the existence of other salt products in the market with similar errors that were not prosecuted, raising questions about the selectivity of prosecution in this case.